Ultrathin Iron Oxide Nanowhiskers as Positive Contrast Agents for Magnetic Resonance Imaging. (1st December 2014) - Macher, Thomas; Totenhagen, John; Sherwood, Jennifer; Qin, Ying; Gurler, Demet; Bolding, Mark S.; Bao, Yuping
<x xml:space="preserve">Abstract</x> In this paper, a highly innovative concept of using ultrathin iron oxide nanowhiskers as a positive (T1) contrast agent for magnetic resonance imaging (MRI) is demonstrated. Iron oxide nanowhiskers with dimensions of approximately 2 nm × 20 nm are synthesized by heating an iron oleate/oleylamine complex under 150 °C. These nanostructures have very high surface‐to‐volume ratios, leading to strong paramagnetic signal, a property suitable for T1 contrast in MRI. The positive contrast enhancement of these nanowhiskers is demonstrated in vitro and in vivo in a rat model. Successful development of this technology has substantial commercial value in biomedical imaging, potentially leading to the advancement of human healthcare technologies.